THE PREVALENCE OF STROKE-ACQUIRED PNEUMONIA IN ICU PATIENTS FOLLOWING A CEREBROVASCULAR ACCIDENT (CVA) - ANWAR, U; ILAHI , I; USMAN, M; KHAN, FL; SALAHUDDIN, HS; ARIF, M (Biological and Clinical Sciences Research Journal, 2024)
Acute ischemic stroke often has a poor clinical prognosis due to its significant complications, including serious pulmonary and neurological problems. Stroke-acquired pneumonia (SAP) refers to any respiratory tract infection developing within 7 days following a stroke. Objective: To determine the actual incidence of SAP in ICU patients. Methods: A descriptive analysis was conducted on stroke patients hospitalized at DHQ City and South City Okara hospitals. Personal data such as name, age, sex, and duration of stroke were collected and recorded on a prepared proforma, along with previous histories of hypertension, diabetes, and smoking. Patients were then transferred to the intensive care unit and observed for three consecutive days. Data were collected if pneumonia associated with a stroke was diagnosed within 72 hours, according to the operating criteria, and recorded on the proforma. Results: Among the 80 stroke patients included in the study, 38 (47.5%) were female and 42 (52.5%) were male. The participants’ average age was 53.75±8.75 years, and the mean duration since stroke onset was 7.42±3.63 hours. SAP was observed in 11 (13.75%) patients. SAP occurred in 6 (15.78%) female patients compared to 5 (11.90%) male patients (p=0.35). SAP was present in 5 (26.3%) diabetic patients versus 6 (9.83%) non-diabetic patients (p=0.14). SAP was detected in 4 (25%) hypertensive patients and 2 (11.7%) patients with a history of smoking, with p-values of 0.41 and 0.37, respectively. SAP was identified in 9 (17.3%) patients with a stroke duration of 6-12 hours. Conclusion: Stroke-associated pneumonia affects more than one in ten patients. Females, individuals with a history of hypertension, and diabetes, and those with a stroke duration of 6 to 12 hours are more likely to develop this condition. However, none of these factors reached statistical significance.